Factors associated with patient adherence to medical recommendations during a health crisis - Anat Reiner-Benaim; Shimon Amar (PLoS ONE, 2026)
Introduction Patient non-adherence to medical recommendations is associated with significant economic and health consequences, particularly in chronic diseases. While less studied, similar implications are also observed for short-term antibiotic treatment non-adherence. A global pandemic creates a complex medical reality with the potential to impact patient adherence, and it is of interest to investigate its effect on patient adherence regarding common community-acquired infectious diseases. This study focused on primary care clinic visits with a diagnosis of fever or cough and followed the performance of referred laboratory tests and chest X-rays and the purchase of prescribed antibiotics, as adherence outcomes. Methods A comprehensive and unique dataset of clinic visits in Southern Israel was used to assess the impact of the pandemic on patient adherence outcomes. We compared the outcomes between the pandemic period and the preceding and succeeding periods and used multivariate modeling to study the impact of the pandemic period on adherence, subject to patient and visit characteristics. Results In total, 609,823 visits were analyzed. Before the pandemic, adherence to throat cultures surpassed that of chest X-ray and referred laboratory tests, and cephalosporins exhibiting higher adherence rates than other antibiotics. Social restrictions and lockdown periods were found to be associated with a decrease in patient adherence. Adherence to referred tests decreased among all patients during social restrictions for complete blood count (Odds Ratio (OR)=0.79, 95%CI = 0.64,0.96), and throat culture (OR=0.64, 95%CI = 0.43,0.93) and among older patients for chest X-ray. Adherence to prescribed antibiotics dropped during social restrictions for penicillin (OR=0.26, 95%CI = 0.17,0.40) and cephalosporins (OR=0.52, 95%CI = 0.32,0.86), but increased for macrolides (OR=2.16, 95%CI = 1.20,3.88). Rural clinics were associated with lower adherence in all outcomes, and visits by phone call were associated with lower adherence, most prominently in throat culture (OR=0.32, 95%CI = 0.26,0.38). Conclusion This study offers a unique contribution to our understanding of patient adherence to acute infection management strategies during a pandemic. The findings illuminate the significant impact of uncertainty on patient adherence to diagnostic testing and antibiotic regimens. Understanding these multifaceted influences is essential for improving patient outcomes and optimizing antibiotics use and resource availability during public health crises.